MBRS-52. TARGETING PRUNE-1 IN A GEMM OF METASTATIC MEDULLOBLASTOMA: A POTENTIAL ROUTE OF INHIBITION FOR NEW FUTURE THERAPIES. Issue 2 (22nd June 2018) - Ferrucci, Veronica; de Antonellis, Pasqualino; Pennino, Francesco Paolo; Asadzadeh, Fatemeh; Siciliano, Roberto; Virgilio, Antonella; Galeone, Aldo; De Martino, Lucia; Quaglietta, Lucia; Errico, Maria Elena; Donofrio, Vittoria; Picard, Daniel; et al.
Abstract: Genetic modifications during development of paediatric Group3 Medulloblastoma (MBGroup3 ) are responsible for its highly metastatic properties and poor patient survival rates. We found PRUNE-1 to be highly expressed in metastatic MBGroup3, which is characterised by TGF-β signalling activation and OTX2 expression. The molecular mechanism was identified underlying the metastatic dissemination of those PRUNE-1-driven-MBGroup3 . PRUNE-1, through its binding to NDPK-A (NME-1), enhances the canonical TGF-β pathway activation, upregulates OTX2 and SNAIL, and inhibits PTEN. We also identified a new non-toxic small molecule pyrimido-pyrimidine derivative (AA7.1) with the ability to enhance PRUNE-1 degradation and to impair tumour progression and metastases in vivo using orthotopic xenograft models with metastatic MBGroup3 cells. Using whole exome sequencing technology in primary human metastatic MB cells, we also defined new deleterious 'non-synonymous homozygous' gene variants with effects on immune cells activation/differentiation, as part of a protein network of relevance for metastatic processes (Ferrucci et al., Brain In Press, 2018). We developed a Genetically Engineered Mouse Model (GEMM) of PRUNE-1-driven-metastatic MB. This GEMM (MATH1-PRUNE-1/Cyclin-B2-LUC) was generated by overexpressing PRUNE-1 in the developing cerebellum (using MATH1 promoter) together with the Luciferase gene (under the control of Cyclin-B2 promoter) in a background TP53 -/-, thus generating Medulloblastoma. Chemotherapeutic drugs for high-risk MB together with AA7.1 were tested in combination on medullospheres showing an impairment of cell index proliferation. In vivo, in xenografted studies, we showed tumour inhibition at both the primary and metastatic sites together with immunonomodulatory effects. Altogether these results are of importance for future targeted therapies of high risk metastatic MBGroup3 .